The Influence Of Dangdut Koplo Deny Caknan Performance Art On Adolescent Cultural Awareness - Sufu Malinda Putri; Yohannes Don Bosco Doho (Eduvest - Journal of Universal Studies, 2024)
Dangdut koplo is a genre of dangdut music that is popular in Indonesia, especially among teenagers. This research aims to determine the influence of Deny Caknan's dangdut koplo performance art on the cultural awareness of teenagers with a correlation study of Deny Caknan's band song entitled Ambyar. Researchers applied quantitative methods in this research. Researchers apply data collection techniques from two aspects, namely method and source. Researchers will analyze the data using correlation analysis and linear regression analysis in this research. The research results show that performing arts has a significant effect on the dependent variable, namely Cultural Awareness. Based on the R-square test hypothesis testing criteria, it can be concluded that the magnitude of 0.600 indicates that the proportion of influence of the Performing Arts variable on the Cultural Awareness variable is 60%. This means that performing arts have a huge influence on cultural awareness. It is proven that every time Deny Caknan's performing arts is held, it is packed with visitors, the majority of whom are young people.